RESPON PERTUMBUHAN DAN HASIL TANAMAN SAWI PAKCOY HIJAU (BRASSICA RAPA L.) TERHADAP PEMBERIAN BERBAGAI PUPUK ORGANIK CAIR (POC) URIN TERNAK - Azzahrotul Fatimah; Umi Barokah (Nusantara Hasana Journal, 2025)
Mustard greens are annual plants belonging to the genus Brassica, with various varieties. One of the most commonly cultivated is green pak choi, which uses the leaves and stems for consumption, either fresh or after being processed. This study aims to observe the effect of administering several types of liquid organic fertilizer (POC) made from livestock urine on the growth and yield of green pak choi. The materials used include Nauli F1 variety pak choi seeds, planting media in the form of soil mixed with rice husk charcoal and manure, and urine-based POC solution from various livestock such as cows, goats, sheep, and rabbits. The experiment was carried out using the non-factorial Completely Randomized Design (CRD) method, and was carried out in Sidobunder Village, Puring District, Kebumen Regency from January to March 2025. The results showed that the use of POC from rabbit urine had the most significant impact on all observed parameters. The tallest plant reached 21.314 cm, the largest number of leaves was 17.2 strands, and the stem diameter reached 1.55 cm. The highest fresh weight of the plant was 95.25 grams, the dry weight was 6.216 grams, and the best fresh weight of the roots was 6.4 grams.